Acrylic expressions painting authentic themes and creating your visual vocabulary - Swider, Staci (Cincinnati, Ohio North Light Books, 2016)
Your artwork is your voice, as unique as your fingerprints, and Acrylic Expressions shows you how to paint and express your authentic self. Learn to create a consistent and individualized body of work through workshop-styel instruction and creative prompts. Discover how to paint intuitively by uncovering meaningful personal symbols and distilling them into a visual vocabulary. Then combine your interpretation and personal inspiration as you use acrylic paints and other materials to create textural, expressive, abstract works of art.
Aspects -- Utterances -- Phrases -- Declarations -- Appearances -- Style -- Accents -- Deliveries -- Voices.
Includes index.
Prof. Jocelyn C. Pinzon (Recommending faculty) - Bookfair2017
Keywords: Acrylic painting -- Technique; Acrylic painting -- Technique